Peran Public Relations pada Program Pangalengan Adventure sebagai Kegiatan Corporate Social Responsibility - Raissa Azzahra Fachya; Maman Suherman (Bandung Conference Series: Public Relations, 2022)
Abstract. Corporate Social Responsibility (CSR) is an activity that must to do by companies in Indonesia. Star Energy Geothemal Wayang Windu Ltd (SEGWWL) as the largest geothermal energy producer in Indonesia carries out CSR activities as well. From the CSR activities, SEGWWL has received various awards. One of which is the CSR Partner Company award from the West Java provincial government. This research aims to know the role of Public Relations especially in Pangelangen Adventure program. The method used in this research is a qualitative method with a case study approach. The data obtained from this research used the methods of interview, observation, documentation, and literature study. The results of this research are: 1) The External Relations Team as a communication mediator between the company and the community regarding Pangalengan Adventure program, communication between the ER and the PA is usually done through whatsapp or informal meetings. 2) The External Relations team as a problem solver in Pangalengan Adventure program bases all decisions and solutions taken to solve problems by conducting discussions between the company and the Pangalengan Adventure team. 3) The External Relations team works on publications for Pangalengan Adventure program by giving advice and editing about the production that carried by the Pangalengan Adventure team. The Pangalengan Adventure team mostly worked on publications for the Pangalengan Adventure. 4) The External Relations team must be involved in CSR activities, especially Pangalengan Adventure program because this is included in the main functions of the External Relations team itself. Abstrak. Corporate Social Responsibiltity (CSR) atau dalam bahasa indonesia disebut Tanggung Jawab Sosial Perusahaan adalah kegiatan yang wajib dilakukan oleh perusahaan di Indonesia. Star Energy Geothemal Wayang Windu Ltd (SEGWWL) sebagai perusahaan produsen energy panas bumi terbesar di Indonesia tentunya melaksanakan kegiatan CSR juga. CSR yang diselenggarakan SEGWWL mendapatkan penghargaan salah satunya adalah penghargaan Perusahaan Mitra CSR dari pemerintah provinsi Jawa Barat. Penelitian ini bertujuan untuk mengetahui bagaimana peran Public Relations SEGWWL dalam program Pangalengan Adventure. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Data yang didapatkan dari penelitian ini menggunakan metode wawancara, observasi, dokumentasi, dan studi pustaka. Hasil dari penelitian ini adalah: 1) Tim External Relations selaku mediator komunikasi antara perusahaan dan masyarakat mengenai program Pangalengan Adventure. Komunikasi yang terjalin antara tim ER dan tim PA biasanya dilakukan melalui media sosial whatsapp atau pertemuan informal. 2) Tim External Relations sebagai pemberi solusi terhadap masalah pada program Pangalengan Adventure mendasarkan seluruh keputusan dan solusi yang diambil untuk menyelesaikan masalah dengan melakukan diskusi antara pihak perusahaan dan tim Pangalengan Adventure. 3) Tim External Relations mengerjakan publikasi untuk program Pangalengan Adventure dengan cara memberikan saran dan masukan mengenai produksi yang telah dilakukan oleh tim Pangalengan Adventure. Tim Pangalengan Adventure lebih banyak mengerjakan publikasi untuk program Pangalengan Adventure sesuai dengan kesepakatan yang telah dibuat. 4) Tim External Relations harus terlibat dalam kegiatan CSR khususnya program Pangalengan Adventure karena hal ini termasuk ke dalam tugas pokok dan fungsi dari tim External Relations sendiri.